FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KECURANGAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN ANALISIS FRAUD HEXAGON - Azizah, Lina; Ridwansyah, Eksa; Kurniawan, Umarudin (LPPM Universitas Bina Bangsa, 2025)
This research was conducted because of the phenomenon of financial statement fraud which has the lowest frequency of cases but has the largest average impact on total losses. Another reason is that there are cases of fraudulent financial reports in banking sector companies. This research aims to determine the influence of the independent variables of financial stability, change of directors, multiple positions, ineffectiveness of supervision, change of auditors, and number of CEO photos on the dependent variable of financial statement fraud. This research is quantitative and uses secondary data, namely the company's annual report. The population in this study are banking companies registered on the IDX for the 2020-2022 research period using purposive sampling data collection techniques. The analysis technique used in this research is logistic regression. The research results show that financial stability, change of directors and holding multiple positions influence financial report fraud. Meanwhile, ineffective supervision, changing auditors, and the number of CEO photos have no effect on financial statement fraud